Analysis of in competition speed skating using IMU's - van der Eb, J.; Mossink, H.; Kiel, E.; Geraets, S.; Veeger, D. J.; Beek, P. J. (ISBS Proceedings Archive (Michigan), 2018)
For feedback to be effective, we must first identify relevant performance indicators for speed skating. We instrumented the skating of 10 junior elite Dutch speed skaters with two inertial measurement units during two competition events. Contact time, stroke frequency and other parameters were derived from collected IMU data and related to performance (finish times). The manner and timing in which the skater initiates a race in the first 100 m, is predictive of the final finish time. A significant correlation was found between finish times and 1) a decrease in stroke frequency and 2) an increase of the contact time of the skate and the ice over the first 100 m of a race. These relations were robust against variations in race distances (i.e., 100, 300, 500 and 1500 m), while the directionality of the relation differed qualitatively between the 100 m sprint and the other distances. We concluded that progression in stroke frequency and contact time are relevant feedback parameters for enhancing performance in speed skating.